1992
DOI: 10.1128/jb.174.1.84-91.1992
|View full text |Cite
|
Sign up to set email alerts
|

The Salmonella typhimurium virulence plasmid complement resistance gene rck is homologous to a family of virulence-related outer membrane protein genes, including pagC and ail

Abstract: A fragment of the Salmonella typhimurium virulence plasmid containing the rck locus, when cloned in the recombinant cosmid pADE016, was shown previously to confer high-level complement resistance on both rough and smooth Escherichia coli, SalmoneUa minnesota, and S. typhimurium and was associated with the production of an outer membrane protein. The outer membrane proteins (OMPs) of gram-negative bacteria provide specialized functions enabling the organisms to interact with the environment, promoting survival.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
109
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(110 citation statements)
references
References 54 publications
0
109
0
1
Order By: Relevance
“…The pagN gene is activated by PhoP and the corresponding protein shares identities with the Hek and Tia invasins/ adhesins of pathogenic E. coli [7]. The Rck protein is encoded by different serovars, including Salmonella Enteritidis and Salmonella Typhimurium, and is a member of a 17-to 19-kDa OMP family involved in cell adhesion and/or invasion including Ail (Yersinia enterocolitica), PagC (Salmonella Typhimurium), OmpX (Enterobacter cloacae) and Lom (bacteriophage lambda-lysogenic E. coli) [11]. Heffernan et al [6] have previously shown that Rck overexpressed in a non-invasive E. coli strain enables the bacteria to adhere to and invade fibroblastic cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pagN gene is activated by PhoP and the corresponding protein shares identities with the Hek and Tia invasins/ adhesins of pathogenic E. coli [7]. The Rck protein is encoded by different serovars, including Salmonella Enteritidis and Salmonella Typhimurium, and is a member of a 17-to 19-kDa OMP family involved in cell adhesion and/or invasion including Ail (Yersinia enterocolitica), PagC (Salmonella Typhimurium), OmpX (Enterobacter cloacae) and Lom (bacteriophage lambda-lysogenic E. coli) [11]. Heffernan et al [6] have previously shown that Rck overexpressed in a non-invasive E. coli strain enables the bacteria to adhere to and invade fibroblastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to adhesion and entry capabilities, Rck also confers a high level of resistance to the bactericidal activity of complement, independent of the lipopolysaccharide (LPS) structure, by inhibiting the polymerization of complement component C9 in the bacterial membrane [9,10]. Rck belongs to a family of five homologous OMP proteins characterized in Salmonella (Rck and PagC), Escherichia coli (Lom), Yersinia enterocolitica (Ail) and Enterobacter cloacae (OmpX) [11]. Molecular analysis has shown that Rck is homologous to PagC and Ail with 53% and 48% identity, respectively, but complement resistance and invasion have been attributed only to Rck and Ail [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One Omp, OmpX, was first described for Enterobacter cloacae (Stoorvogel et al, 1991), but homologues, including PagC, Lom, Rck and Ail (the attachment-invasion locus protein of Yersinia spp. ), were identified in other Gram-negative bacteria (Dupont et al, 2004;Heffernan et al, 1992a;Mecsas et al, 1995). Proteins in this family promote invasion, resistance to complementmediated killing, survival in macrophages, and internalization in epithelial cells (Cirillo et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Ail belongs to a family of highly conserved 17-19-kDa outer membrane proteins found in the Enterobacteriaceae, including Rck (Salmonella typhimurium and enteritidis), PagC (typhoid and nontyphoid Salmonella, Escherichia coli O157:H7), and OmpX (E. coli and Enterobacter cloacae) (13,14). All of these proteins have virulence-associated phenotypes.…”
mentioning
confidence: 99%